INDEKS KEANEKARAGAMAN SERANGAN HAMA PADA EKOSISTEM TANAMAN MEN GHASILKAN KELAPA SAWIT (Elaeis guineensis Jacq) DI DIVISII KEBUN SEI PARIT PT. SIDO JADI - Sulthon Parinduri; Marshal Arifin Sinaga; Muhammad Irfan Mulyana (Jurnal Agro Estate, 2017)
Oil palm is a strong plant, although this plant is also not sparedfrom attacks ofpests and diseases, both less harmful and harmful.Pest Caterpillar Fire is the most pest that attacks because the pest is the most difficultpest in its control. Firefly pests multiply rapidly andfeed on the leaves until they havefinished all the leaves o f palm oil so that the characteristics o f thepest attack can be easily identified. The research was carried out in Division I Sei Parit Estate PT. SIDO JADI Sei Rampah DistrictSerdangBerdagai with data retrieval secondary.Research time fo r 5 months, from January-May 2016. Research use descriptive analysis method ofprimary data collection by way o fdirectfield survey to identify the characteristics o f pests by counting the number ofsubject stricken pests. Secondary data takenfrom the DivisionlPT. SIDO JADI. The results showed the diversity ofpest attack on oil palm Division 1 Sei Parit Estate is classified low i.e.H < 1 = 0,401.